What is the cost of privatization for workers? - Martin Olsson; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2018)
The world is in the midst of a new wave of privatization, with record dollar amounts raised in both developed and developing countries.Using rich Swedish registry data covering two decades from the mid-1990s, we show that privatizations increased unemployment incidence by almost a fifth, and duration by a quarter, relative to peers who remained employed by a state-owned enterprise. This led to almost one million extra days of unemployment for the workers affected. Wages and labor force participation remain unchanged.Furthermore, we show that privatizations have been costly for workers, and therefore for society, only if they took place during recessions. These results shed new light on the welfare costs of privatization and how they can be mitigated.
Keywords: F66; J24; J63; L33; M51; 330; Employment; Privatization; State-owned enterprises (SOEs); Unemployment